Agent-based simulation of ethnic prejudice transmission using Entorama tool - Srbljinović, Armano (2008)
The work describes implementation of an agent-based model of ethnic prejudice transmission by means of Entorama multi-agent modelling and simulation tool. The model is grounded in social psychological theories of group behaviour and the influences of groups on individual behaviour, as well as in ascriptive theories of ethnicity, underlining the role of society members themselves in creating and maintaining social pressures towards increasing social importance of ethnicity. The model enables representation of the way interpersonal contacts at micro-level give rise to global patterns of prejudice at macro-level. The model’ s use is envisioned in testing the basic principles of contact theory, including the claim that contact is a factor which only amplifies or reduces the effects of other influencing factors, as well as the assertion that whether the impact of contact will be actualized as amplification or reduction depends on the nature of other factors present in situations in which contact occurs.